2022
DOI: 10.31744/einstein_journal/2022ao6648
|View full text |Cite
|
Sign up to set email alerts
|

Body dissatisfaction among undergraduate medical students in the city of Juiz de Fora, Minas Gerais, Brazil

Abstract: Objective: To assess the level of body dissatisfaction among undergraduate medical students in the city of Juiz de Fora, Minas Gerais, Brazil. Methods: A cross-sectional study with 232 volunteers of both sexes at a private college. The Body Shape Questionnaire was used, which is a tool based on the sum of values that allow classifying body dissatisfaction according to the following scores: less than 111, if absence of body dissatisfaction; between 111 and 138, if mild body dissatisfaction; between 139 and 167,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The results showed that participants self-reported inadequate knowledge regarding appearance-specific care and wanted access to an accredited course [ 60 ]. Additionally, multiple studies indicate that high degree of body image dissatisfaction and inaccurate perceptions exists among students within health-related fields, such as medical students [ 61 , 62 ], nursing students [ 63 ], and pharmacy students [ 64 ]. Therefore, future research should not only further explore whether DIF exists between educational level but also between participants’ study majors (e.g., health-related vs. non-health-related).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that participants self-reported inadequate knowledge regarding appearance-specific care and wanted access to an accredited course [ 60 ]. Additionally, multiple studies indicate that high degree of body image dissatisfaction and inaccurate perceptions exists among students within health-related fields, such as medical students [ 61 , 62 ], nursing students [ 63 ], and pharmacy students [ 64 ]. Therefore, future research should not only further explore whether DIF exists between educational level but also between participants’ study majors (e.g., health-related vs. non-health-related).…”
Section: Discussionmentioning
confidence: 99%